INTERNATIONAL EXPERIENCE IN ENSURING THE QUALITY AND COMPETITIVENESS OF FOOD PRODUCTS (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
This article describes the activities and international experience of developed countries in ensuring the quality and safety of food products and their competitiveness. The role and significance of food in the human body is indicated. The negative effect of harmful and toxic substances on the human body is indicated. The analysis of ways to provide the population with food is carried out. An analysis of the work carried out in the Republic of Uzbekistan to ensure the quality and safety of agricultural and food products is made, recommendations are given for raising them to a new level of provision.